Vaccine confidence plummets in the Philippines following dengue vaccine scare: why it matters to pandemic preparedness. Issue 3 (4th March 2019) - Larson, Heidi J; Hartigan-Go, Kenneth; de Figueiredo, Alexandre
ABSTRACT: In November 2017, it was announced that the new dengue vaccine ("Dengvaxia") had risks for those not previously exposed to dengue. While some countries proceeded with adjusting guidance accordingly, the Philippines reacted with outrage and political turmoil with naming and shaming of government officials involved in purchasing the vaccine, as well as scientists involved in the vaccine trials and assessment. The result was broken public trust around the dengue vaccine as well heightened anxiety around vaccines in general. The Vaccine Confidence Project TM measured the impact of this crisis, comparing confidence levels in 2015, before the incident, with levels in 2018. The findings reflect a dramatic drop in vaccine confidence from 93% "strongly agreeing" that vaccines are important in 2015 to 32% in 2018. There was a drop in confidence in those strongly agreeing that vaccines are safe from 82% in 2015 to only 21% in 2018; similarly confidence in the effectiveness of vaccines dropped from 82% in 2015 to only 22%. This article highlights the importance of routinely identifying gaps or breakdowns in public confidence in order to rebuild trust, before a pandemic threat, when societal and political cooperation with be key to an effective response.